Registration of two new parasites Choricotyle scapularis and Dactylogyrus sp. on the gills of Dentex macrophthalmus Fish in the Coastal Water of Lattakia–Syria. - ناصيف محمد; تغريد لايقة; بدر العلي (Latakia University Journal -Biological Sciences Series, 2023)
The current study aimed to investigate the infection with Monogenea ectoparasites that infect Dentex macrophthalmus in the Syrian Marine Water and to determine the prevalence rates and mean intensity of infection isolated from this fish, which in turn contributes to the enrichment of the database of fish parasites in the Syrian Marine Water. Where 115 individuals were collected from the locations of Ras Al-Baseet, and the Port of Fishing during the period from the beginning of June 2021 to the end of June 2022. The external organs (gills, oral cavity) of all caught fish samples were examined to detect infection with external parasites. In this research, the two parasites: Choricotyle scapularis (Diclidophoridae) and Dactylogyrus sp. (Dactylogyridae) were isolated from the gills of Dentex macrophthalmus fish, where the number of infected fish with these two parasites was 8 out of 115 Dentex macrophthalmus fish examined. The number of fish infected with the parasitic species C. scapularis was 4 fish distributed as follows: (1, 3) infected fish at the locations of Ras Al-Baseet, the Port of Fishing respectively, with total rate of infection (16.6)% at the location of Ras Al-Baseet and (32.2)% at the location of the Port of Fishing.While the total intensity of infection was (1, 2.5) parasite/fish at Ras Al-Baseet, the Port of Fishing respectively. The number of infected fish with the parasite Dactylogyrus sp. was 4 fish distributed as follows: (1, 3) infected fish in the locations of Ras Al-Baseet, the Port of Fishing respectively, with a total rate of infection (16.6) % and (32.2)%, and with a total intensity of infection (1, 2.5) parasite/fish at Ras Al-Baseet, the Port of Fishing respectively. This is the first time that these ectoparasites have been isolated from Dentex macrophthalmus Fish in the Syrian Marine Water. The highest Percentage and Intensity of infection were recorded during Summer and Spring for: Choricotyle scapularis, Dactylogyrus sp. in the both locations.